EFFECTIVENESS OF USING AUTHENTIC MATERIALS IN TEACHING FOREIGN LANGUAGES - Matyokubova, Shokhida (Журнал иностранных языков и лингвистики, 2023)
In this article we discuss about the effectiveness of using authentic (real) tea munching in the material and learning foreign languages, especially English which is high in the educational institutions of the authentic materials in the language learning process. Authentic learning foreign language material to help both the developers and enlarges the learner's worldview in any field. In addition, this article analyzes the effective method of “social learning and cultural competence of the academic lyceum students from authentic materials in the foreign language munching tea video for” learn any language is learning proficiency comes from a (non-native language).